The Right to Family Reunification of Children Seeking International Protection under the Convention on the Rights of the Child: Misplaced Reliance on Travaux?. (20th September 2022) - Ioffe, Yulia
Abstract: This article focuses on a unique provision, article 9 of the Convention on the Rights of the Child (CRC), which stipulates a right to family reunification for all children, including those seeking international protection. Relying on the rules of treaty interpretation of the Vienna Convention on the Law of Treaties (VCLT), the article argues that the desirable interpretation of article 9 prescribes a positive obligation upon States to provide entry to the territory of a State for the purposes of family unity. It also challenges the prevailing academic view that only article 10 of the CRC applies in the migration context, while article 9 of the CRC is applicable exclusively within State borders. The article contends that the text of these provisions, as well as the context of the CRC, does not support the opinion of a considerable number of scholars, who argue that children seeking international protection fall outside the scope of article 9 of the CRC. It suggests that the interpretation of article 9 of the CRC, using the proper interpretative methodology of the VCLT, demands the articulation of a distinctive child-centred approach to family reunification and a presumption against family separation of children seeking international protection.